Аналіз розрахунків пов’язаних каналів для деяких гало систем - Hussain, F.M.; Majeed, F.A.; Meteab, M.H. (Publishing house "Academperiodika", 2020)
The fusion reaction for systems involving halo nuclei are investigated by two- and multicoupled channel calculations for the systems 8B+58Ni, 11Be+209Bi, and 15C+232Th. The effect of coupling between the breakup channel and the elastic channel have been considered using the Continuum Discretized Coupled Channels (CDCC) method in full quantum and semiclassical approaches. The calculation of the fusion cross-section qfus (mb), fusion barrier distribution Dfus (mb/MeV) and fusion probability Pfus reproduces the measured data for the systems under study quite well above and below the Coulomb barrier VB. In the case of two-channel coupling both in semiclassical and quantum mechanical approaches, the measured data above the Coulomb barrier VB are overestimated.